Indian time: time, seasonality, and culture in Traditional Ecological Knowledge of climate change - Chisholm Hatfield, Samantha; Marino, Elizabeth; Whyte, Kyle Powys; Dello, Kathie D.; Mote, Philip W. (Ecological processes, 2018)
Introduction Western climate science and Traditional Ecological Knowledge (TEK) represent complementary and overlapping views of the causes and consequences of change. In particular, observations of changes in abundance, distribution, phenology, or behavior of the natural environment (including plants and animals) can have a rich cultural and spiritual interpretation in Indigenous communities that may not be present in western science epistemologies. Results Using interviews with Indigenous elders and other Traditional Knowledge holders, we demonstrate that assumptions about the nature, perception, and utilization of time and timing can differ across knowledge systems in regard to climate change. Conclusions Our interviewees’ focus on relationality predisposes them to notice interactional changes among humans and other species, to be sensitive to smaller scale examples of change, to be more likely to see climate change as part of a broader time scale, and to link changes to a greater suite of socio-political phenomena, including the long arc of colonialism. One implication of this research and the interactions among humans and other species is that policies restricting Native and non-Native access to resources (i.e., hunting and fishing) to certain calendar seasons may need to be revisited in a changing climate.